Evaluasi Kinerja Penyelenggaraan Pelayanan Terhadap Kepuasan Masyarakat Di Kecamatan Sawahan Kota Surabaya - Nurul Komaria; Anggraeny Puspaningtyas (Lembaga Pengembangan Kinerja Dosen, 2024)
Public service is a series of activities in the form of goods, services, and or administrative services carried out by public service providers. As the organizer and implementer of public services, the state is obliged to provide public services properly and optimally. Evaluation is needed as a form of improvement in improving the performance of public service providers so that public satisfaction occurs. The purpose of this study is to analyze the performance of public service delivery in the District. This research uses a qualitative type with a descriptive approach. The data used in this research is in the form of primary data obtained from interviews with the community and staff in Sawahan Subdistrict and direct observation in the field, while secondary data is collected from various sources. The results of this study found that in improving the performance of public service delivery in Sawahan Sub-district, a Community Satisfaction Survey and a Public Consultation Forum were carried out in increasing community satisfaction.